Complex regional pain syndrome induced by pacemaker implantation for sick sinus syndrome. Issue 6 (2nd October 2017) - Kisanuki, Megumi; Fujita, Kazumasa; Moriyama, Shohei; Irie, Kei; Yosida, Chiharu; Fukata, Mitsuhiro; Arita, Takeshi; Yokoyama, Taku; Odashiro, Keita; Maruyama, Toru; Akashi, Koichi
Abstract: A 53‐year‐old woman reported burning pain, muscle weakness, and dysesthesia of the left arm 2 months after permanent pacemaker insertion in the ipsilateral side for the treatment of sick sinus syndrome. Complex regional pain syndrome (CRPS) induced by pacemaker implantation was diagnosed. In 2017, her pulse generator became exhausted and was exchanged carefully to avoid exacerbation of CRPS, under the application of local anesthesia and premedication. Six months later, the patient's grip strength in her left hand remained lower relative to that in her right hand. Although rare, the presence of CRPS following device implantation should be remembered.